Respuesta :
It can be noted from the given that a = 1, b = -8 and c = -9. To transpose c to the other side of the equation, all that needs to be done is to add 9 to both sides of the equation,
x² - 8x -9 + 9 = 0 + 9
The answer would be,
x² - 8x = 9
x² - 8x -9 + 9 = 0 + 9
The answer would be,
x² - 8x = 9
By using Bhaskara's formula we will see that the solutions are x = 9 and x = -1
How to solve a quadratic equation?
Remember that for a quadratic equation of the form:
x^2 + b*x + c = 0
The solutions are given by Bhasakara's formula:
[tex]x = \frac{-b \pm \sqrt{b^2 - 4*a*c} }{2*a}[/tex]
In this case, we want to write:
x^2 + b*x = c
Then we want to replace c by -c in the formula.
So we start with:
x^2 - 8x - 9 = 0
We add 9 in both sides:
x^2 - 8x = 9.
Now using Bhaskara's formula we get:
[tex]x = \frac{8 \pm \sqrt{(-8)^2 - 4*1*(-9)} }{2*1} \\\\x = \frac{8 \pm 10 }{2}[/tex]
Then the two solutions are:
- x = (8 + 10)/2 = 9
- x = (8 - 10)/2 = -1
If you want to learn more about quadratic equations, you can read:
https://brainly.com/question/1214333